ANALISIS GERAK TARI MERAK SUBAL KARYA S. MARIDI PADA SANGGAR SOERYO SOEMIRAT DI SURAKARTA - Endra Sabekti; Didik Bambang Wahyudi (Greget, 2020)
The research titled "Analysis of Merak Subal Dance Movement by S. Maridi at Soeryo Soemirat Gallery in Surakarta", was created by S. Maridi in the 1969s. Merak Subal Dance is a dance that represents the life (behavior) of peacocks. S. Maridi's Merak Subal dance was inspired by sundanese peacock dance.This study aims to describe and analyze the movements in The Merak Subal Dance. The research method used is descriptive analytics with qualitative data properties, namely collecting data through observations, interviews, subsequent library studies analyzed descriptively. The research problems were analyzed using conceptual foundations from Soedarsono on dance forms and Agus Tasman on the analysis of dance moves and characters.The results of Merak Subal Dance research in Soeryo Soemirat gallery showed that the dance was presented in the form of a group dance drawn by three dancers with a duration of about eight minutes. Elements that make up The Merak Subal Dance are motion, floor design(floor pattern), top design, dramatic design, theme, makeup and fashion, dance music, property, lighting, venue and performance time. Then the analysis of motion includes materials, energy, space, time, organization, aggregation, character, description. Keywords: Merak Subal Dance, choreography, Soeryo Soemirat gallery.